Proposals on Improvement of System of Local Elections by Open Party Lists - VORONA, Petro V.; PAKHOMOVA, Milana V.; KACHAN, Yana V.; MISHCHENKO, Kateryna S.; ZOZULIA, Valentyna A. (Journal of Advanced Research in Law and Economics, 2019)
The electoral system is the means by which the process of the exercise of power by the people takes place, the content of which is extremely important for the nature of the representative mandate and the special functioning of the institution of constitutional responsibility in the system of representative bodies. The article disclosures the features of local elections by open party lists and emphasizes the problematic issues of the electoral legislation that do not contribute to full and ‘incorruptible’ expression of will of citizens and to the effective formation of local authorities. The main approach to studying this problem is descriptive method that reveals the peculiarities of providing gender equality, distribution of authorities at the local level and rights of citizens to participate in local elections not only through political parties. Materials of the article have practical value for lecturers of universities of economic and legal specialties.